The influence of physical activity on the thinking of schoolchildren - Polevoy, Georgiy Georgievich (Bangladesh Journal of Medical Science, 2023)
Objective: to determine the influence of physical activity in physical education classes on the thinking indicators of schoolchildren. Methods: This was a cross-sectional study conducted in a secondary school in Russia, it was attended by ninth graders aged 15-16 years in the number of 141 schoolchildren. The main method of research was the test “Cross out an extra word”, which determines the level of development of students’ thinking. The test was used before and after the physical education lesson 1 time per month for 5 months. Statistical analysis used: The student’s T-criterion was used in the study. Results: children who did not engage in physical education in the classroom were not able to significantly improve their performance in the test, which indicates a possible adaptation to the test after its first performance before the lesson. Children who were engaged in physical exercises were able to significantly increase the test results. Conclusion: the effectiveness of the influence of a physical education lesson at school on thinking indicators. This study will serve as an additional motivation for children to engage in physical culture, since the impact of physical exercises has a positive impact not only on the development of physical qualities, but also on the development of schoolchildren’s thinking. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 612-616